A Conceptual Framework of Relationship between Human Resource practices and Employee Turnover Intention. - Danial Akhtar Sumbal (SEISENSE Journal of Management, 2018)
Turnover intention has attained substantial consideration in last few decades and has been comprehensively studied because of its deep implications towards today’s organization. Current study attempts to examine the relationship between Human Resource practices and turnover intentions by taking moderating effect of personality traits. This conceptual framework takes into account one dependent variable i.e. Turnover Intention and three independent variables i.e. Pay Satisfaction, Performance Appraisals, Career Management and two moderating variables i.e. Neuroticism, Extroversion.